2016
DOI: 10.1038/srep22509
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphatic mRNA vaccine induces CD8 T-cell responses that inhibit the growth of mucosally located tumours

Abstract: The lack of appropriate mouse models is likely one of the reasons of a limited translational success rate of therapeutic vaccines against cervical cancer, as rapidly growing ectopic tumours are commonly used for preclinical studies. In this work, we demonstrate that the tumour microenvironment of TC-1 tumours differs significantly depending on the anatomical location of tumour lesions (i.e. subcutaneously, in the lungs and in the genital tract). Our data demonstrate that E7-TriMix mRNA vaccine-induced CD8+ T l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 65 publications
6
51
0
Order By: Relevance
“…The formulation of E7‐TM (TriMix) vaccine was described previously . The sequence encoding the full‐length human SOX2 protein (NCBI Reference Sequence: NG_009080.1) was cloned in‐frame between the signal sequence and the transmembrane and cytoplasmic regions of human DC‐LAMP.…”
Section: Methodsmentioning
confidence: 99%
“…The formulation of E7‐TM (TriMix) vaccine was described previously . The sequence encoding the full‐length human SOX2 protein (NCBI Reference Sequence: NG_009080.1) was cloned in‐frame between the signal sequence and the transmembrane and cytoplasmic regions of human DC‐LAMP.…”
Section: Methodsmentioning
confidence: 99%
“…Incorporation of the TriMix adjuvant into intranodal injections of mice with mRNAs encoding tumour-associated antigens resulted in potent antigen-specific CTL responses and tumour control in multiple tumour models 133 . A more recent study demonstrated that intranodal injection of mRNA encoding the E7 protein of human papillomavirus (HPV) 16 with TriMix increased the number of tumour-infiltrating CD8 + T cells and inhibited the growth of an E7-expressing tumour model in mice 67 .…”
Section: Mrna Cancer Vaccinesmentioning
confidence: 99%
“…For example, cisplatin treatment significantly increased the therapeutic effect of immunizing with mRNA encoding the HPV16 E7 oncoprotein and TriMix, leading to the complete rejection of female genital tract tumours in a mouse model 67 . Notably, it has also been suggested that treatment with antibodies against programmed cell death protein 1 (PD1) increased the efficacy of a neoepitope mRNA-based vaccine against metastatic melanoma in humans, but more data are required to explore this hypothesis 68 .…”
Section: Mrna Cancer Vaccinesmentioning
confidence: 99%
“…Intranodal injections of RNA-based cancer vaccines showed induction of very strong Ag-specific T-cell responses in mice [74]. However, we found that using this route of administration for a CPP-based therapeutic cancer vaccine generated an Ag-specific immune response of lower magnitude compared to the s.c. route (our unpublished observations).…”
Section: Route Of Administration Of Cpp-based Cancer Vaccinesmentioning
confidence: 99%